Peran Stakeholder Dalam Pengembangan Wisata Budaya Pada Desa Wisata Munggu, Kecamatan Mengwi, Kabupaten Badung - Githa Prami, Ni Nyoman Srimurti; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2021)
Munggu Village is one of tourist village in Badung Regency. There are Mekotek Tradition as cultural tourism in Munggu Tourist Village and still found problems related to development of cultural tourism so the role of stakeholders is needed. Aims of this study is to determine the role of stakeholders in development of cultural tourism. This research uses descriptive qualitative method. Technique of determining informants is purposive sampling. The development of cultural tourism in Munggu Tourist Village was in the form of a program to encourage tourism activities and there are stakeholders who take part in it. The role of stakeholders and relationship between stakeholders has not been optimal. This is shown by the fact that problems are still being encountered in the implementation of the role of Munggu Village Government and Pokdarwis Warisan Pusaka. Relationship between stakeholders still creates problems and it has impacts on sustainability of program development. Keywords : Stakeholder Roles, Munggu Tourism Village, Tourism Village Development